Genomic differences between sequence types 1 and 104 of Streptococcus suis Serotype 2 - Kerdsin, Anusak; Takeuchi, Dan; Akeda, Yukihiro; Nakamura, Shota; Gottschalk, Marcelo; Oishi, Kazunori (PeerJ, 2022)
Background Streptococcus suis is a zoonotic pathogen that can cause invasive infections in humans who are in close contact with infected pigs or contaminated pork-derived products. S. suis serotype 2 sequence type (ST) 1 strains are mostly associated with meningitis, whereas ST104 strains are mostly recovered from sepsis cases in humans. No data are available for comparison of the ST1 and ST104 strains at the genomic level, particularly concerning virulence-associated genes. Thus, genomic comparison of both STs was performed in this study. Methods An ST1 isolate (ID26154) from the cerebrospinal fluid of a patient with meningitis and an ST104 isolate (ID24525) from the blood of a patient with sepsis were subjected to shotgun pyrosequencing using the 454 GS Junior System. Genomic comparison was conducted between the ST1 isolate and the ST104 isolate using the Artemis Comparison Tool (ACT) to identify the region of differences (RDs) between ST1 and ST104. Results Fifty-eight RDs were unique to the ST104 genome and were mainly involved in metabolism and cell functional activities, cell wall anchored proteins, bacteriophages and mobile genetic elements, ABC-type transporters, two-component signal transductions, and lantibiotic proteins. Some virulence genes mostly found in ST1 strains were also present in the ST104 genome. Whole-genome comparison is a powerful tool for identifying genomic region differences between different STs of S. suis serotype 2, leading to the identification of the molecular basis of virulence involved in the pathogenesis of the infection.
Keywords: Streptococcus suis; Genome; Sequence type; Region of difference; Virulence-associated gene